ANALISIS IMPLEMENTASI PROGRAM SEKOLAH RAKYAT DALAM PEMENUHAN HAK ATAS PENDIDIKAN BERDASARKAN PASAL 31 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DI KOTA JAMBI - Nurtati Ritonga, Sri; Aditya Candra, Alif; Tiara Maulia, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The right to education is a constitutional right guaranteed by Article 31 of the 1945 Constitution of the Republic of Indonesia. However, its implementation still faces various obstacles, such as poverty and high school dropout rates, including in Jambi City. This study aims to analyze the implementation of the "Sekolah Rakyat" (People's School) Program in fulfilling the right to education in Jambi City. The research employs a qualitative approach, with data collection techniques including interviews, observations, and documentation. The results indicate that the Sekolah Rakyat Program plays a vital role in providing educational access for underprivileged children through a free, dormitory-based education system. Nevertheless, its execution still encounters challenges, such as limited resources and program reach. Consequently, the Sekolah Rakyat Program serves as a strategic alternative in supporting educational equality, though it still requires optimization in its implementation.